Existence and death: A philosophical approach to the poetry of César Vallejo and Vicente Aleixandre - Kouadio, Djoko Luis Stéphane (2021)
The poetic writings of the Spanish poet Vicente Aleixandre and the Peruvian César Vallejo are characterized by dealing with themes of existentialist philosophers regarding the human condition marked by death. Both poets, although belonging to different spaces, are united in the expression of lyricism and socio-political commitment, which refers to a call for responsibility in the face of the problems arising from the human condition.